GENDER EQUALITY AND CHILDREN’S EQUALITY IN LIBERAL AND CONSERVATIVE DISCOURSES: IMPLICATIONS TOWARD LANGUAGE AND SOCIETY - ODROWĄŻ-COATES, ANNA (Society Register, 2019)
This introductory article is intended to open the volume of work prepared by the participants of the 12th UNESCO Janusz Korczak Chair International Summer School. The participants presented these papers at the RC25 ISA Interim International Conference in Warsaw, entitled: "Language and Society. Research Advances in Social Sciences" (26-27.09.2019), exploring the concepts of gender equality and children's equality in liberal and conservative discourses and practices invested in language. The papers in this volume primarily use the methodology of discourse analysis and a range of tools and methods within this framework. The purpose is to shed light on how discourses inform preferences, behaviours and representations, towards the positioning of individuals in society, based on their respective gender and their individual status - whether an adult or a child. It is interesting to explore what is expected of the holders of these positions and whether they are able to confront and renegotiate their situation. The authors look into gendered childhood, analysing if differences can be found in so-called conservative and liberal discourses. The gender aspect of childhood and the resistance towards children’s expected positions interlinked to their gender is visible to diverse degrees in this selection of papers. The concept of social positioning due to one's gender is at the heart of this volume. Therefore, this Editorial forms a theoretical backstage for the volume of works included in the special post-conference issue of Society Register.